1870 Md. Laws 892, ch. 473 §§ 1-2 - (:unkn) unknown (General Publisher, 1870)
Anyone arrested for any crime or misdemeanor and found to have any pistol, dirk-knife, Bowie-Knife, slingshot, billy, brass, iron, or any other metal knuckles, razor, or any other deadly weapon whatsoever. Violators fined not less than three but no more than ten dollars.
--
Keywords: COMMITTING CRIME W/ WEAPON